Novel microfluidic paper-based analytical devices (μPADs) for the determination of nitrate and nitrite in human saliva - Ferreira, Francisca T.S.M. (2022)
In this work, two different microfluidic paper-based analytical devices (μPADs) were developed for the quantification of nitrite and nitrate in human saliva samples, in order to aid in the diagnosis of some diseases and health conditions associated with these ions. The development of these nitrite and nitrate μPADs involved several studies to optimize their design and construction, including an interference assessment and stability studies. These μPADs allowed a nitrite determination in a range of 5–250 μM with limits of detection and quantification of 0.05 μM and 0.17 μM, respectively, and a nitrate determination in the range 0.2–1.2 mM with limits of detection and quantification of 0.08 mM and 0.27 mM, respectively. As for the stability, both of the μPADs were stable when stored in vacuum at 4 °C (the nitrite μPAD for at least 60 days and the nitrate μPAD for at least of 14 days) and, after the sample placement, the nitrite and nitrate μPADs could be scanned within the first 4 and 2 h, respectively. The nitrite μPAD measurements were compared with the ones obtained from the standard colorimetric method and there were no statistically significant differences between these two methods. To evaluate the accuracy of nitrate μPAD measurements, 4 certified water samples were used and recovery studies using saliva samples were performed.